Formation of easterly wind maxima at 200 mb during southwest monsoon - SINGH, RANJIT (MAUSAM, 1985)
In three case studies presented, the formation of easterly wind maxima at 200 mb south of the monsoon depressions can be explained with the help of conservation of angular momentum when the northeasterly air stream emerging from the cloud system acquires the additional easterly momentum during Its motion towards southwest. The temperature gradients from north to south occur at 300, 250 and 200 mb across these wind maxima. In one of the case studies the subsidence warming on the equator ward leg of the monsoon cell splits the jet stream, has been elucidated in the vertical cross-section presented.